Pirate queen : the legend of Grace O'Malley - Lee, Tony, 1970- (Candlewick Press, 2020)
When Ireland suffers under the rule of Henry VIII, Grace O'Malley takes to the seas after her husband's murder and gains a reputation as the Pirate Queen of Ireland and confronts Queen Elizabeth I.